Effects of Cast-Iron Surface Texturing on the Anti-Scuffing Performance under Starved Lubrication - Li, Wenhua (Materials (Basel), 2019)
Advances in heavy-duty diesel engine designs place higher demands on the friction and wear performance of the piston ring and cylinder liner (PRCL) interface. The potential of using micro-textures machined on the whole stroke of a cast-iron cylinder liner was investigated in this work. A set of running-in and starved lubrication experiments was performed using a custom reciprocating test rig that imparts a combination of combustion-level pressures and the resulting impacts. Based on a comparison of micro-dimple parameters, the friction coefficient for the running-in period at the shocking dead center was the smallest at a designed combination of 1000-μm diameter, 22% area fraction, and arrangement with half-radius intersecting distance of two adjacent micro-dimple columns. The non-scuffing time under starvation was the longest at a designed combination of the following parameters: 800 μm diameter, 22% area fraction, and quarter-radius intersecting distance arrangement. From finite element analysis, it was found that stress concentrates at the micro-dimple periphery and at the connections between adjacent micro-dimples. However, surface topography examination showed that scuffing initiates in the non-dimpled regions between the micro-dimpled columns rather than at their edges. Finally, under reciprocating motion, micro-dimples can collect wear debris to inhibit further propagation of scuffing in the micro-dimpled region.